Reason versus Emotion in Anita Desai’s Cry, the Peacock - Neupane, Khagendra (Cognition, 2019)
Anita Desai’s Cry, the Peacock portrays a conflict between emotion and reason. Maya, the married woman, carries emotional values whereas her husband, Gautama, embodies rational ideals.She falls a prey to the patriarchy. She gets disillusioned when she realizes being distanced by male members, whom she considers her protectors. As a result, she turns neurotic and murders her husband. The murderous instinct grows out of her deserted life, together with the sense of her insecurity resulted from an astrologer’s prediction of her or her husband’s death four years after their marriage.